2013
DOI: 10.1007/s10926-013-9475-4
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a Multidisciplinary Care Program for Patients Undergoing Gynaecological Surgery

Abstract: Purpose This study describes the process evaluation of an innovative multidisciplinary care program for patients undergoing benign gynaecologic surgery. This care program aims at improving recovery and preventing delayed return to work and consists of two steps: (1) an interactive e-health intervention for all participants, and (2) integrated clinical and occupational care management for those participants whose sick leave exceeds 10 weeks. Methods Eligible for this study were employed women aged between 18–65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
2
26
1
1
Order By: Relevance
“…This renders the clinical relevance of the effect sizes from our quantitative analysis questionable. In contrast, clinically relevant improvements in QoL are described after integrated care interventions, compared with usual care, among non-surgical back pain patients41 42 and patients undergoing abdominal or gynaecological surgeries 43–45. Studies reporting on interventions of e/mHealth34 35 and, in particular in combination with active referral or goal setting,24 showed additional effectiveness in reducing pain and pain interference.…”
Section: Discussionmentioning
confidence: 99%
“…This renders the clinical relevance of the effect sizes from our quantitative analysis questionable. In contrast, clinically relevant improvements in QoL are described after integrated care interventions, compared with usual care, among non-surgical back pain patients41 42 and patients undergoing abdominal or gynaecological surgeries 43–45. Studies reporting on interventions of e/mHealth34 35 and, in particular in combination with active referral or goal setting,24 showed additional effectiveness in reducing pain and pain interference.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that e-health is a suitable way of delivering self-management interventions for various conditions, including cancer [ 20 , 21 ], and to deal with various problems, including return to work [ 22 , 23 ]. In addition, e-health proved suitable for delivering an integrative-care management intervention as well [ 24 ]. Based on these findings, we choose to deliver the intervention as an e-health intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, collaboration can also be established using a secure website, where stakeholders can work together toward a common goal and share the necessary information to achieve this. In the eHealth intervention developed by Vonk Noordegraaf et al [ 14 ], almost half of the participants invited their supervisor to be involved in the eHealth intervention and that approximately 60% of the supervisors took this opportunity [ 30 ].…”
Section: Methodsmentioning
confidence: 99%